The Paradigm Reconstruction of Indonesian Judge’s Thought of Law in Adjudicating Criminal Cases - Handayani, Henny Timira (The Indonesian Journal of International Clinical Legal Education, 2019)
The Indonesian Criminal Act Code (Kitab Undang-Undang HukumPidana/ KUHP) based on the positivistic paradigm that is directed byprinciple of legality, as the expression of deductive syllogisms:regulations as a major premise should be filled in by the facts whichrevealed as the premise minor to conclude the punishment or not. Butthe positivistic paradigm could not always be complied with changesin Indonesian plural society. The KUHP still applies the theory ofmonistic. The prove on the entire outline of the criminal element, isproving the existence unlawfulness and at the same time prove thefault/ criminal liability, unless there is a reason the criminal removal. Butpeople demands the new criteria assessment of fairness: 1) liability notonly based on fault, but also the material of justification, 2) the criminalact was not only base on formal unlawfulness, but also materialunlawfulness, and 3) punishment should fit the balance of people andindividual interests. That demand required the judge thought of lawother than just of positivistic. This article analyzed the change ofIndonesian judges‟ paradigm of thought on criminal law, the causesinfluenced, and the efforts that could reconstructed the fairnessparadigm. This paper used double type of research technics, doctrinalresearch at once and empirical research, which used data collectiontechniques of the study of librarianship, observation and interview.